PELIBATAN MASYARAKAT UNSUR 5K DALAM IMPLEMENTASI YOGYAKARTA SMART CITY - Rizky Akhirunnisyah; Roychansyah, M. Sani (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2026)
The implementation of Smart City aims to improve the economy, quality of life and community welfare. Based on data from Yogyakarta City as one of the pilot projects of the 100 Smart City movement, the objectives of Smart City development have not been optimally realized in Yogyakarta City. Community involvement is key in the success of Smart City implementation, but the top-down development of Smart City has an impact on the lack of public literacy related to Smart City and results in the lack of utilization of Smart City products in Yogyakarta City. Based on the Smart City Masterplan document, the implementation of Smart City in Yogyakarta City always involves the community in 5K elements, namely Kota, Kampung, Kampus, Komunitas and Korporat. This research aims to identify the extent of citizen engagement in the implementation of Smart City in Yogyakarta City with qualitative research methods, data collection through interviews, field observations, and documentation studies with interactive data analysis techniques. The results showed that the increase in Smart City literacy and the utilization of Smart City technology in general in Yogyakarta City is still lacking. The engagement of 5K elements is included in the high engagement spectrum, namely the spectrum of citizen engagement at the collaboration level. The high level of engagement of the 5K element is more dominant in programs in the dimensions of smart branding and smart society, but the 5K element tends not to know that these activities are part of the Smart City program in Yogyakarta City because there is no notification from the implementing OPD and the Smart City program in Yogyakarta City tends to be related to tourism and community-driven local economy. Therefore, the involvement of the 5K element does not directly implicate the literacy of the general public in the development and utilization of Smart City products in Yogyakarta City.